Comparing Robot-Assisted Laparoscopic Pyeloplasty vs. Laparoscopic Pyeloplasty in Infants Aged 12 Months or Less - Wong, Yuenshan Sammi; Pang, Kristine Kit Yi; Tam, Yuk Him (Frontiers in Pediatrics, 2021)
Objective: To investigate the outcomes of minimally invasive approach to infants with ureteropelvic junction (UPJ) obstruction by comparing the two surgical modalities of robot-assisted laparoscopic pyeloplasty (RALP) and laparoscopic pyeloplasty (LP). Methods: We conducted a retrospective review of all consecutive infants aged ≤12 months who underwent either LP or RALP in a single institution over the period of 2008–Jul 2020. We included primary pyeloplasty cases that were performed by or under the supervision of the same surgeon. Results: Forty-six infants (LP = 22; RALP = 24) were included with medians of age and body weight at 6 months (2–12months) and 8.0 kg (5.4–10 kg), respectively. There was no difference between the two groups in the patients' demographics and pre-operative characteristics. All infants underwent LP or RALP successfully without conversion to open surgery. None had intraoperative complications. Operative time (OT) was 242 min (SD = 59) in LP, compared with 225 min (SD = 39) of RALP (p = 0.25). Linear regression analysis showed a significant trend of decrease in OT with increasing case experience of RALP(p = 0.005). No difference was noted in the post-operative analgesic requirement. RALP was associated with a shorter hospital length of stay than LP (3 vs. 3.8 days; p = 0.009). 4/22(18%) LP and 3/24(13%) RALP developed post-operative complications (p = 0.59), mostly minor and stent-related. The success rates were 20/22 (91%) in LP and 23/24 (96%) in RALP (p = 0.49). Conclusions: Pyeloplasty by minimally invasive approach is safe and effective in the infant population. RALP may have superiority over LP in infants with its faster recovery and a more manageable learning curve to acquire the skills.